2010
DOI: 10.1186/1472-6807-10-s1-s6
|View full text |Cite
|
Sign up to set email alerts
|

Mining for the antibody-antigen interacting associations that predict the B cell epitopes

Abstract: BackgroundPredicting B-cell epitopes is very important for designing vaccines and drugs to fight against the infectious agents. However, due to the high complexity of this problem, previous prediction methods that focus on linear and conformational epitope prediction are both unsatisfactory. In addition, antigen interacting with antibody is context dependent and the coarse binary classification of antigen residues into epitope and non-epitope without the corresponding antibody may not reveal the biological rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
55
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 34 publications
4
55
0
Order By: Relevance
“…Another frequently investigated feature of the B-cell epitope is the amino acid composition (Andersen et al, 2006; Ofran et al, 2008; Rubinstein et al, 2008; Sun et al, 2011; Zhao and Li, 2010). It is generally agreed that epitopes are enriched in charged and polar amino acids and depleted of aliphatic hydrophobic amino acids, when comparing the epitope amino acid distribution to either the entire PDB database (Ofran et al, 2008) or amino acid composition of the antigen as a whole (Andersen et al, 2006; Zhao and Li, 2010) Furthermore, by recognizing that epitopes usually reside on the protein surface, Rubinstein et al (2008) suggested that the amino acids Tyr and Trp are significantly over-represented in epitopes and that Val is significantly depleted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another frequently investigated feature of the B-cell epitope is the amino acid composition (Andersen et al, 2006; Ofran et al, 2008; Rubinstein et al, 2008; Sun et al, 2011; Zhao and Li, 2010). It is generally agreed that epitopes are enriched in charged and polar amino acids and depleted of aliphatic hydrophobic amino acids, when comparing the epitope amino acid distribution to either the entire PDB database (Ofran et al, 2008) or amino acid composition of the antigen as a whole (Andersen et al, 2006; Zhao and Li, 2010) Furthermore, by recognizing that epitopes usually reside on the protein surface, Rubinstein et al (2008) suggested that the amino acids Tyr and Trp are significantly over-represented in epitopes and that Val is significantly depleted.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally agreed that epitopes are enriched in charged and polar amino acids and depleted of aliphatic hydrophobic amino acids, when comparing the epitope amino acid distribution to either the entire PDB database (Ofran et al, 2008) or amino acid composition of the antigen as a whole (Andersen et al, 2006; Zhao and Li, 2010) Furthermore, by recognizing that epitopes usually reside on the protein surface, Rubinstein et al (2008) suggested that the amino acids Tyr and Trp are significantly over-represented in epitopes and that Val is significantly depleted. Besides individual amino acid preferences in epitopes, specific amino acid pairs have been observed more frequently in both linear (sequence based studies) (Chen et al, 2007) and conformational (structural based studies) (Rubinstein et al, 2008; Sun et al, 2011; Zhao and Li, 2010) epitopes than in non-epitope areas, suggesting that some amino acid pairs work cooperatively in mediating antibody binding. The concept of amino acid cooperatively has been adopted from studies on protein:protein interfaces, where pairs of hydrophobic and polar amino acids have been argued to play an important role in the binding formation (Lijnzaad and Argos, 1997; Ma et al, 2003; Neuvirth et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A number of researchers have reported identifying CR of Abs and Ags by analysis of publicly available crystal structures (10)(11)(12). A large body of work in this field is aimed at identifying CR as a means of developing algorithms for predicting B cell epitopes (10,(13)(14)(15)(16)(17), whereas others have focused on analyzing or predicting CR in CDR of Abs (8,(18)(19)(20). The majority of the existing studies define two residues to be in contact when they are within a specified distance of each other.…”
mentioning
confidence: 99%
“…The majority of the existing studies define two residues to be in contact when they are within a specified distance of each other. Many researchers use 4 Å as the definition of CR (10,(14)(15)(16)(17), and the Molecular Modeling Database (21), at the National Center for Biotechnology Information, defines protein interactions using a 4-Å cutoff. One group has published several works using 6 Å (13,20,22) and reported that their conclusions were unaffected by cutoffs ranging from 4 to 6 Å (20).…”
mentioning
confidence: 99%
“…Therefore, specificity as defined for a monovalent binding event can diverge from specificity as it is defined for higher-order interactions. A corollary of this conclusion is that the composition of epitopes and paratopes, defined in terms of the structural elements for which substitutions have an effect on the specificity-defining measurement, can differ in different contexts despite complete conservation of the structures that physically make direct contact [79][80][81]. Specificity in the molecular recognition between proteins and their interacting partners is thought to be essential in underlying the biochemistry of living organisms, whereas promiscuity is often associated with unwanted side effects, poor catalytic properties, and errors in biological function [82].…”
Section: Methods Used To Isolate Quantify and Characterize Cytokinementioning
confidence: 82%